PENGARUH KONFLIK PERAN GANDA DAN STRES KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT. SURYAMAS AKURASI CIKARANG) - Endah Prihartini; Dadang Sudirno; Hani Sri Mulyani; Rina Nur'aini (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The success and achievement of company goals is highly dependent on employeeperformance. It is expected that employees will work at optimal levels to achieve the desiredresults. However, they also face the challenge of balancing dual roles as both employees andparents, responsible for their families and work. This situation leads to multiple role conflicts,causing work stress and negatively impacting performance. This study aims to examine theimpact of multiple role conflicts and work stress on the performance of employees at PT.Suryamas Accuracy Cikarang, either independently or collectively.The research method employed in this study is survey-based, utilizing a descriptive andverification analysis approach. Through distributing questionnaires, data was collected. studypopulation consisted of 52 employees from PT. Suryamas Accuracy Cikarang, and thesaturated sample technique was used. Multiple linear regression analysis was the analyticaltool utilized in this study. It involved testing classical assumptions, determining the coefficientof determination, and conducting hypothesis testing.The findings from this study indicate that both multiple role conflicts and work stresssignificantly affect the performance of employees at PT. Suryamas Accuracy Cikarang, eitherindividually or collectively